Nursing actions to promote mental health in the senescence process: integrative review - Frazão , Karla Yhanne Fonseca; Santos , Larissa Fernanda Menezes dos; Albuquerque, Ingrid de Campos; Costa, Larissa Di Leo Nogueira; Abreu, Thaysa Gois Trinta; Soeiro, Vanessa Moreira da Silva (Disciplinarum Scientia | Saúde, 2025)
Introduction: In Brazil, the term “elderly” applies to people aged 60 or over due to the increase in life expectancy, which has led to an increase in this population in the country. Attention to the mental health of the elderly is crucial to improving their quality of life. Despite negative associations with old age, such as finitude and inactivity, elderly people seek to actively participate in different areas and reaffirm their rights in society. Objective: To analyze, in light of the literature, evidence regarding nursing actions for the care and maintenance of the mental health of elderly people during the senescence process. Methodology: This is an integrative literature review with articles published in the period 2014-2023, selected through online access using the databases: SciELO, LILACS and BDEnf. Results: Seven selected articles emphasized the importance of social interaction for elderly people, allowing them to share their experiences and feel valued in solving daily challenges. Furthermore, they highlighted the practice of physical activities and carrying out daily tasks as essential for maintaining mental health during aging. Conclusion: The nurse plays a central role in the advancement of these initiatives, especially in primary health care, being responsible for facilitating moments of interaction and listening with the elderly, guiding both the elderly and the family about the individual’s autonomy in their daily activities and promote well-being in old age.